HUBUNGAN EFIKASI DIRI MINAT DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PJOK SMP NEGERI 2 CIMANGGUNG - Riski 789 (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
The background of this research is related to the problem of low student learning outcomes in PJOK subjects. This is due to the lack of self-efficacy, low interest and learning motivation of students so that their learning outcomes become less. This study aims to determine the relationship between self-efficacy, interest and learning motivation with PJOK learning outcomes. The formulation of the problem in this research are: (1) Is there a relationship between self-efficacy and PJOK learning outcomes. (2) Is there a relationship of interest with PJOK learning outcomes. (3) Is there a relationship between learning motivation and PJOK learning outcomes? (4) How big is the relationship between self-efficacy, interest and motivation to learn with PJOK learning outcomes together. Respondents involved in this study were students of SMP Negeri 2 Cimanggung with a total of 82 students who were taken based on probability sampling technique; simple random sampling. Data collection techniques used by using questionnaires and documentation. The data analysis technique used to test the hypothesis is the product moment correlation technique and multiple correlation analysis using self-efficacy variables (X1), interest (X2) motivation (X2) as the independent variable and the dependent variable learning outcomes (Y). The results showed that (1) there was a positive and significant relationship between self-efficacy and PJOK learning outcomes, where rcount was 0.348, while rtable with N=82 at the 5% significance level was 0.176, so rcount was greater than rtable (0.348 > 0.176 ). (2) there is a positive and significant relationship between interest and PJOK learning outcomes, where rcount is 0.348, while rtable with N=82 at the 5% significance level is 0.176, so rcount is greater than rtable (0.348 > 0.176). (3) there is a positive and significant relationship between self-efficacy and CHD learning outcomes, where rcount is 0.348, while rtable with N=82 at the 5% significance level is 0.176, so rcount is greater than rtable (0.348 > 0.176). (4) there is a positive and significant relationship between self-efficacy, interest and motivation to learn with PJOK learning outcomes, where rcount is 0.348, while rtable with N=82 at 5% significance level is 0.176, so rcount is greater than rtable (0.348 > 0.176).